STUDI LITERASI MATEMATIS - Erdy Poernomo; Lia Kurniawati; Khamida Siti Nur Atiqoh (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
The need for good literacy, especially mathematical literacy in the industrial era 4.0 and the low international assessment are the main concerns for Indonesia. The study aims is to provide an overview of mathematical literacy and numeracy literacy from various sources. The research method used is descriptive qualitative. Sources of data come from various relevant documents collected through library sources. The result of the study found that mathematical iteration and numeracy literacy have a close relationship when viewed from the scope of context, competence, and content. In terms of context, both mathematical literacy and numeracy literacy have the same scope, namely personal, work, social, and scientific. In terms of competence, all competencies in numeracy literacy are included in mathematical literacy. Mathematical literacy has 3 competencies that are not possessed by numeracy literacy including communication, mathematizing, and devising strategies for solving problems. In terms of content, all content in numeracy literacy is included in mathematical literacy. Mathematical literacy has 7 contents that are not owned by numeracy literacy including functions, algebraic expressions, equations and inequalities, co-ordinate systems, counting principles, data variability and its description, and samples and sampling.